2020
DOI: 10.1080/17457289.2020.1814309
|View full text |Cite
|
Sign up to set email alerts
|

Conspiratorial thinking and foreign policy views: evidence from Central Europe

Abstract: Foreign policy analysts assume that conspiratorial thinking is linked to citizens' foreign policy views and in particular to a preference among citizens for an alignment with Russia rather than the West. Empirical studies on the relationship between conspiratorial thinking and citizens' foreign policy views are, however, lacking, despite a growing general academic interest in its origins and consequences. Our analysis breaks new ground by empirically evaluating the relationship between conspiratorial thinking … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 43 publications
1
7
0
Order By: Relevance
“…In this way, individuals are predisposed to see the world as the one where ‘authoritative accounts [are] fabricated and powerful actors [are] conspirators’ (Edelson et al, 2017: 936). In line with recent research, we argue that those who score high on conspiratorial thinking tend to attach conspiratorial explanations to political events, which in turn influences their political attitudes (see also Douglas et al, 2019 ; Onderco and Stoeckel, 2020 ).…”
Section: Crisis-specific Explanationssupporting
confidence: 89%
“…In this way, individuals are predisposed to see the world as the one where ‘authoritative accounts [are] fabricated and powerful actors [are] conspirators’ (Edelson et al, 2017: 936). In line with recent research, we argue that those who score high on conspiratorial thinking tend to attach conspiratorial explanations to political events, which in turn influences their political attitudes (see also Douglas et al, 2019 ; Onderco and Stoeckel, 2020 ).…”
Section: Crisis-specific Explanationssupporting
confidence: 89%
“…Seeing the world as governed by conspiracies increased the intentions to engage in illegal political actions (such as participation in illegal demonstrations or committing a violent attack) but attenuated the willingness to engage in legal forms of political participation (e.g., voting or joining a political party; Imhoff et al, 2021 ). Moreover, belief in conspiracy theories makes it possible to anticipate unconventional (but non-violent) participation ( Ardèvol-Abreu et al, 2020 ), justification of protest actions ( Chayinska and Minescu, 2018 ), support for leaving the EU ( Jolley et al, 2021 ), support for Brexit ( Swami et al, 2018 ), foreign policy views ( Onderco and Stoeckel, 2020 ), and Stealth Democracy beliefs ( Pantazi et al, 2021 ). CBs were also associated with self-reported voting behavior in the 2016 Italian constitutional referendum ( Mancosu et al, 2021 ) and voting behavior with regard to the election of Donald Trump ( Lamberty et al, 2018 ).…”
Section: Resultsmentioning
confidence: 99%
“…Truth Decay, conspiracy theories, and conspiratorial thinking within the politic or public of U.S. allies can affect U.S. national security. Limited academic evidence shows that conspiracy theories can shift public views on alliances-such as research that has shown a shift away from the West toward Russia in Slovakia (Onderco and Stoeckel, 2020). This indicates that Truth Decay in U.S. allies could serve as a blow to alliance strength.…”
Section: Us Financial Support Of Nato M U Lt I N At I O N a L R E L A...mentioning
confidence: 99%